Increasing the level of formation of educational motivation and cognitive independence in the study of natural sciences - Larisa A. Filipovich; Irina G. Kondaurova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The formation of students personal qualities aimed at learning, gaining new knowledge and skills to use this knowledge if necessary, is impossible without realizing the importance of the learning process for each student personally. Interest in educational activities and in the process of cognition itself, understanding of educational material can be formed only by using active, creative teaching methods. In our work, the use of practice-oriented tasks in the study of disciplines of the natural science cycle was considered. We suppose that in order to form and activate the interest of students in the study of natural sciences, it is necessary to model production problem situations that are solved with the help of knowledge and skills acquired in the classroom. If students understand how they can practically apply the theoretical knowledge gained in the classroom in their professional activities, then the study of complex material becomes more understandable and interesting. We distinguish two personal qualities of students, which prevail over others when considering the learning process educational motivation and cognitive independence. It is necessary not only to form these qualities, but also to activate them in every possible way in the learning process for the successful acquisition of knowledge and skills that will be useful to a future specialist in his professional activity. The aim of the research was to determine whether the use of practice-oriented tasks has an impact on the formation and activation of students learning motivation and cognitive independence. The results of the study confirmed that the use of practice-oriented tasks in the study of disciplines of the natural science cycle has a positive impact on the formation and activation of students educational motivation and cognitive independence.